2017
DOI: 10.5152/tud.2016.93467
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of Urologists and Gynecologists about overactive bladder and treatment of it in Turkey: A questionnaire survey

Abstract: Objective: We aimed to review the approaches of urologist and gynecologist in the management of overactive bladder (OAB). Material and methods:A questionnaire consisting of 12 items were answered by 375 urologist and 46 gynecologist. The differences between frequency of encountering OAB, their viewpoints concerning conservative treatment, and their experience related to anticholinergic drug use and the management of refractory OAB were compared. Results:The majority of the urologists, and gynecologists respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…It was interesting to note that bladder diaries were utilized only in half of the patients who were included to our study, although they are the mainstay of behavioral treatment. In a recent survey, it was reported that urologists requested bladder diary for only 23.9% of their OAB patients . However, this study included some weak points, such as the unclear questionnaire delivery method, unknown response rate and absence of observation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It was interesting to note that bladder diaries were utilized only in half of the patients who were included to our study, although they are the mainstay of behavioral treatment. In a recent survey, it was reported that urologists requested bladder diary for only 23.9% of their OAB patients . However, this study included some weak points, such as the unclear questionnaire delivery method, unknown response rate and absence of observation.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent survey, it was reported that urologists requested bladder diary for only 23.9% of their OAB patients. 13 However, this study included some weak points, such as the unclear questionnaire delivery method, unknown response rate and absence of observation. One of the strengths of our study was that the routine behavior of the urologists was assessed without any external influence.…”
Section: Discussionmentioning
confidence: 97%
“…[ 12 13 ] This compares favorably with the 24% response rate in one of the surveys from Europe. [ 14 ] However, the poor utilization of patient-reported outcome measures needs to be addressed. Such measures are important since UI is a quality of life problem.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] In contrast, a survey in Europe showed that 68.8% urologists chose to perform UDS only when patients were refractory to the drug therapy. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation